Pengaruh Pengawasan Terhadap Penanggulangan Penyalahgunaan Narkoba Di Balai Rehabilitasi Badan Narkotika Nasional Baddoka Kota Makassar - Rahayu, Anita; Hakim, Lukman; Usman, Jaelan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine the effect of supervision on the prevention of drug abuse in the Baddoka National Narcotics Agency Makassar City and focused on drug abuse control in the Baddoka National Narcotics Agency Rehabilitation Center Makassar City. This study used a quantitative sample of 53 people by using saturated sampling so that the total number of employees was sampled. Data were collected by using a questionnaire instrument. The data was analyzed quantitatively using simple linear regression. The results of this study indicated that the influence of supervision of drug abuse prevention at the National Narcotics Agency Baddoka Makassar Rehabilitation Agency, there was a significant influence between control and drug control. Therefore, the hypothesis in the study was accepted because it was supported by the significance value. Furthermore supervision of the employee was also influenced by direct and indirect supervision techniques.